DETERMINING FACTORS OF PATIENT SATISFACTION WITH PHARMACEUTICAL SERVICES: A SYSTEMATIC REVIEW - Satrio Dwi Ramadhan; Chairun Widyaningsih; Anna Wahyuni (Journal Pharmaceutical Science and Application, 2024)
Background: Good pharmaceutical service quality can be seen through the level of patient satisfaction. Patient satisfaction is a feeling that arises from the performance of healthcare services obtained after patients compare them with their expectations and their needs are met. Pharmaceutical services still have shortcomings and require continuous improvement to enhance trust and minimize patient disappointment. Objective: The purpose of this systematic review was to identify and gather evidence related to the factors that determine patient satisfaction. Methods: This systematic review follows the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Information collection was conducted through searches on PubMed, Scopus, and Google Scholar from 2018 to 2023, considering eligibility and inclusion criteria. Results: Eight studies have been identified that provide various determining factors of satisfaction, including 10 factors based on patient characteristics: age, gender, education, job, salary, race, marital status, religion, disease status, and visit. Additionally, there were eight determining factors based on pharmaceutical service providers: location, facilities, medication, pharmacy services, working time, waiting time, assurance, and additional non-paid services. Conclusion: The study identified and collected evidence related to the determining factors of patient satisfaction from 2018 to 2023, along with the reasons from each article. The determinants of satisfaction based on these factors can be considered by pharmacists when determining errors that need to be corrected and services that need improvement. Keywords: Determinant; Patient Satisfaction; Patient Characteristic; Pharmaceutical Service; PRISMA